Fibrin-Associated, EBV-Negative Diffuse Large B-Cell Lymphoma Arising in Atrial Myxoma: Expanding the Spectrum of the Entity. (February 2022) - Baugh, Laura; Brown, Noah; Song, Joo Y.; Pandya, Shreyash; Montoya, Vernon; Perry, Anamarija M.
Fibrin-associated diffuse large B-cell lymphoma (FA-DLBCL) is a provisional entity in the 2017 Revision of the World Health Organization Classification. This indolent entity, which is frequently discovered incidentally, is currently classified under the category of diffuse large B-cell lymphoma associated with chronic inflammation (DLBCL-CI), an aggressive lymphoma with poor survival. Several authors have proposed that it be classified separately since, in contrast to DLBCL-CI, transformation to aggressive lymphoma has rarely been reported and this entity has distinct clinical and histological features. We describe a rare case of a 62-year-old male with FA-DLBCL associated with atrial myxoma, which was incidentally discovered. In contrast to typically described immunophenotypic features of this entity, that is, activated B-cell phenotype (ABC) and Epstein-Barr virus (EBV) positivity, our case showed germinal center B-cell (GCB) phenotype and was EBV negative. Clinical staging revealed no evidence of lymphoma elsewhere in the body, and the patient did not receive adjuvant chemotherapy after surgical excision and remains in remission. This case illustrates that occasionally FA-DLBCL can show GCB phenotype, as opposed to the typical ABC phenotype. Moreover, we propose that the definition of the entity be expanded to include EBV-negative cases.